Forest Development and Interactions with Large Herbivores - Kalén, Christer (Christer Kalen, Ecology Building, Lund University, 223 62 LUND, 2004)
This thesis discusses aspects of feeding habits of moose (Alces alces) and their impact on forest development. The development of forage that is available to moose was studied by sampling the amount of edible biomass on pine and birch trees. A strong relationship was found between foliage (and twig) biomass and tree diameter, which corroborates the hypothesis that sapwood area limits the amount of leaves that can be supported by a tree. The vertical distribution of crown biomass could be described with a sinusoidal function. Tree diameter, tree height, the vertical length of the crown and the physical constraints of the animal determine the amount of available food. The diet preferences of the moose result in uneven browsing patterns in forest landscapes. A managed forest area was studied with respect to twig consumption, and it was found that trees were not consumed in proportion to availability. The probability that the most preferred species (rowan, aspen and willow) would be selected for browsing was found to be about 14 times higher than the corresponding probabilities for Scots pine or downy birch, and about three times higher than for common juniper and silver birch. Spruce was strongly avoided by the moose. When the resource value of a tree was defined by both its preference value and amount of biomass we were able to explain more of the spatial distribution than if biomass was accounted for alone. By introducing browsing into an individual-based gap model (FORSKA) the long-term impact of browsing in a forest stand was studied. As browsing intensity increased, the relative abundance of preferred tree species decreased. Tree species composition was more or less linearly related to browsing intensity. Hence, the impact of browsing on tree species composition is dependent not just on browsing intensity and abiotic factors such as climate, but also on the animals' preference for different tree species. The optimal balance between browsing damage and recreational hunting was addressed by developing a ...